(untitled) (Fiep Bulletin - online, 2015)
This work has as objective to analyze the repercussion of the end of the Match Liberating of America, in a source communication printed (Periodical Leaf of São Paulo). In this context we look for to verify, which the number of pages destined to the match in question, as well as evidencing which the tied marks, the heroes and the result of the related games. To understand the process observed, we use of the theory of the fields as analysis tool. Of this form, we thus search to go beyond practical of the modality the soccer, but to also verify the possibilities beyond the game.